Detection of Ampicillin, its Sodium Salt and Alkaline Hydrolysis Products by MALDI-TOF Mass Spectrometry - Lukáš Hleba; Attila Kántor; Jana Petrová; Miroslava Kačániová (Scientific Papers Animal Science and Biotechnologies, 2023)
Antibiotic resistance of bacteria is very big problem in clinical and veterinary medicine in recent year. This problem is increasing by the exposure of bacteria against antibiotics. The most spread of resistance is resistance against penicillins antibiotics. Ampicillin is common use antibiotic in the both medicine. Therefore, detection of antibiotics and antibiotic resistance are very important for prevention of spread of antibiotics in the environment and resistant bacteria too. Therefore the aim of this study was detection of ampicillin, its sodium salts and alkaline hydrolysis products by MALDI-TOF Mass Spectrometry. For detection of pure ampicillin, its sodium salts and alkaline hydrolysed products MALDI-TOF MS (Matrix Assisted Light Desorption Ionization – Time of Flight Mass Spectrometry) Microflex LT in positive ion mode was used. Determined mass spectra were observed by FlexAnalysis software. The mass spectra and molecular weight of ampicillin, its sodium salts and hydrolysed products were compared with theoretical molecular weight of these compounds. The results showed that it is possible to detect ampicillin, its sodium salts and hydrolyzed products by MALDI-TOF MS in positive ion mode with some correction in analytical software. This knowledge is resulting that MALDI-TOF MS detection method can be useful for detection of ampicillin from different kind of environment samples and it is possible to detect ampicillin resistance mechanism (enzymatic destruction) indirectly, because resistance against penicillins is enzymatic hydrolysis of beta-lactam core. Also the most important issue is that method is very quickly and cheap.